2015
DOI: 10.1002/j.0022-0337.2015.79.12.tb06044.x
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Using E4D Compare's “% Comparison” to Assess Crown Preparations in Preclinical Dental Education

Abstract: When a dental school is deciding which technology to introduce into a curriculum, it is important to identify the educational goals for the system. The authors' primary goal for the use of a computer-aided resource was to offer students another way to assess their performance, to enhance their learning, and to potentially decrease their learning curve in the preclinical environment prior to using the technique in clinical patient care. The aim of this study was to examine the validity of the "% Comparison" num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Software‐generated comparison percentages calculated by virtual comparison of student preparations versus a standard preparation have been suggested as a reliable and consistent method of student assessment (Renne et al, ). However, to date, no correlation has been found between faculty assessments of student work and comparison percentages (Callan, Haywood, Cooper, Furness, & Looney, ).…”
Section: Introductionmentioning
confidence: 99%
“…Software‐generated comparison percentages calculated by virtual comparison of student preparations versus a standard preparation have been suggested as a reliable and consistent method of student assessment (Renne et al, ). However, to date, no correlation has been found between faculty assessments of student work and comparison percentages (Callan, Haywood, Cooper, Furness, & Looney, ).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the numerical comparison generated by the software is more precise than faculty assessments. However, in , Callan, Haywood, Cooper, Furness, and Looney found no correlation between faculty assessments and the percentage comparison values computed by the software. This discrepancy may arise from the fact that the percentage comparison feature does not assess numerous criteria considered fundamental to tooth preparation that are assessed by faculty.…”
Section: Introductionmentioning
confidence: 93%
“…In this context, companies, specialized in CAD/CAM technology (Computer Aided Design/Computer Aided Manufacturing), developed specific teaching software to evaluate the quality of dental preparation realized on physical simulation model, with a high number of manageable parameters. Assessment of such system proved to be of great educational value, 1 , 2 and this software is also used for teaching oral cavities in restorative dentistry and dental anatomy. 3 , 4 It turned out to be a very interesting preclinical teaching tool.…”
Section: To the Editormentioning
confidence: 99%